Comprehensive Analysis of the Role of Mobile Application Gamification in Science Education for Motivation and Knowledge Retention - Prasetya, Muhammad Gibran Alif; Yasin, Ahmad Alfian Risydan (Journal Mobile Technologies (JMS), 2026)
Low student motivation and knowledge retention in abstract science concepts remain significant challenges in modern science education. This study aims to comprehensively analyze the role of mobile application gamification in enhancing student engagement and strengthening long-term memory. The method employed is a Systematic Literature Review (SLR) following the PRISMA 2020 protocol, involving a rigorous selection of 10 reputable international journal articles (Scopus Q1-Q4) published between 2020 and 2026. Findings indicate that competitive elements, such as leaderboards, significantly trigger intrinsic motivation, while interactive visualizations through AR and simulations effectively improve knowledge retention by simplifying complex cognitive concepts. Despite a identified research gap regarding long-term sustainability in resource-limited environments, this study concludes that a balanced integration of visual aesthetics and pedagogical depth fosters sustainable mastery of science concepts. These results provide strategic contributions for educators in designing evidence-based, inclusive, and adaptive learning media.